L'ara portàtil de Sant Pere de Rodes. Hipòtesi de filiació longobarda - Sanjosé i Llongueras, Lourdes de (Miscel·lània litúrgica catalana, 2018)
The purpose of this article is to examine the portable altar of Sant Pere de Rodes Monastery with the aim of providing a relevant chronological context. We analyze human (angel) and plant motifs that comprise the front and back of the altar, and recreate drawings of these items in two separate plates. We then compare these to other pieces in different art genres like sculpture, manuscripts and precious metalworks. Having compared the altar's motifs to those of the other art pieces and having identified some unique characteristics, we contend that the altar should be considered a piece of Longobard art originating in the North of the Italian Peninsula at some point between the 8th and 9th centúries.